2015
DOI: 10.1002/art.38967
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Intestinal Dysbiosis in Ankylosing Spondylitis

Abstract: Objective. Ankylosing spondylitis (AS) is a common, highly heritable immune-mediated arthropathy that occurs in genetically susceptible individuals exposed to an unknown but likely ubiquitous environmental trigger. There is a close relationship between the gut and spondyloarthritis, as exemplified in patients with reactive arthritis, in whom a typically self-limiting arthropathy follows either a gastrointestinal or urogenital infection. Microbial involvement in AS has been suggested; however, no definitive lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
278
3
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(314 citation statements)
references
References 15 publications
21
278
3
12
Order By: Relevance
“…Specifically, Rikenellaceae family members were depleted in patients who had chronic HIV infection relative to HIV-uninfected controls (46) and suppressed in IBD patients relative to healthy controls (45,47). Conversely, one study reported a higher abundance of Ruminococcaceae and Rikenellaceae and a decrease in the abundance of Prevotellaceae in the terminal ileum microbiota of subjects with ankylosing spondylitis (AS) compared with healthy controls (48).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Rikenellaceae family members were depleted in patients who had chronic HIV infection relative to HIV-uninfected controls (46) and suppressed in IBD patients relative to healthy controls (45,47). Conversely, one study reported a higher abundance of Ruminococcaceae and Rikenellaceae and a decrease in the abundance of Prevotellaceae in the terminal ileum microbiota of subjects with ankylosing spondylitis (AS) compared with healthy controls (48).…”
Section: Discussionmentioning
confidence: 99%
“…Появились новые доказательства, свидетельствую-щие в поддержку теории, что измененная синантропная микрофлора является фактором инициации и поддержа-ния хронического воспаления при таких заболеваниях, как псориаз, воспалительные заболевания кишечника (ВЗК) и СпА [8,9,[23][24][25][26].…”
Section: микробиом человекаunclassified
“…С развитием метода секвенирования были проведены ряд исследований по изучению отклонений в разнообра-зии микрофлоры кишечника у больных анкилозирующим спондилитом (АС), псориатическим артритом (ПсА), псо-риазом и ВЗК с внекишечными проявлениями [9,23,26,[34][35][36].…”
Section: микробиом кишечника и спондилоартритыunclassified
See 1 more Smart Citation
“…Novel high-throughput DNA sequencing methodologies, together with ever-expanding bioinformatics and computational capabilities, now allow for recognition of bacterial taxons without the need for tedious, inefficient culturing approaches. These efforts have led to several studies showing gut microbiome alterations (a term known as dysbiosis) characterizing multiple autoimmune rheumatic conditions, including RA 21 , AS 22 , and psoriatic arthritis 23 . One such report specifically identified a decrease in Faecalibacterium prausnitzii in the stool of children with enthesitis-related arthritis compared to controls 24 .…”
mentioning
confidence: 99%